A 4‐MicroRNA signature can discriminate primary lymphomas from anaplastic carcinomas in thyroid cytology smears. Issue 4 (10th December 2013) - Fassina, Ambrogio; Cappellesso, Rocco; Simonato, Francesca; Siri, Maayan; Ventura, Laura; Tosato, Francesca; Busund, Lill‐Tove; Pelizzo, Maria Rosa; Fassan, Matteo
<x xml:space="preserve">Abstract</x> BACKGROUND Anaplastic thyroid carcinoma (ATC) and primary thyroid lymphoma (PTL) are uncommon tumors of the thyroid gland with several overlapping clinical and pathologic features that may render their differentiation difficult in fine‐needle aspiration (FNA) cytology. MicroRNA (miRNA) signatures have been recently reported as useful diagnostic tools applied to cytology specimens. METHODS Smears of 23 ATCs, 14 PTLs, and 20 non‐neoplastic materials with multinodular goiter (MNG) were retrieved and classified based on their cytologic features and flow cytometric profiles. The ATC‐related expression of hsa‐miR‐26a, hsa‐miR‐146b, hsa‐miR‐221, and hsa‐miR‐222 was quantified using quantitative reverse transcriptase‐polymerase chain reaction analysis. RESULTS All miRNAs were remarkably up‐regulated in ATC samples compared with PTL samples (P < .01). Moreover, expression levels of hsa‐miR‐146b, hsa‐miR‐221, and hsa‐miR‐222 were significantly higher in ATCs than in MNG samples (P < .01). Significant down‐regulation of hsa‐miR‐26a was observed in PTLs compared with MNG samples, whereas hsa‐miR‐146b was overexpressed. Receiver operating characteristic analysis was used to determine the optimal cutoff for distinguishing ATC from PTL. The estimated receiver operating characteristic thresholds displayed a sensitivity level greater than 0.80 in achieving a diagnosis of PTL, allowing the correct identification of 13 of 14 PTL samples (93%). CONCLUSIONS Histotype‐specific miRNA signatures can provide new insight into the molecular mechanisms of thyroid carcinogenesis. The tested 4‐miRNA signature is a promising diagnostic tool for differentiating ATC from PTL and non‐neoplastic MNG, even in the presence of scant material obtained from minimally invasive procedures. Cancer (Cancer Cytopathol) 2014;122:274–281. © 2013 American Cancer Society.